1988
DOI: 10.1002/jcp.1041340112
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic stimulation of human breast cancer cells in a growth factor‐defined medium: Synergistic action of insulin and estrogen

Abstract: The cooperative action of 17 beta-estradiol (E2) and polypeptide growth factors in stimulating proliferation of human breast cancer cells in vitro was investigated. To prevent background estrogenic stimulation, only phenol red-free media were used. When cultured in media supplemented with steroid-stripped serum in which all polypeptide growth factor activity had been chemically inactivated, MCF7 cells were unable to proliferate and became virtually quiescent. In the additional presence of insulin, epidermal gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
89
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(95 citation statements)
references
References 28 publications
5
89
0
1
Order By: Relevance
“…1A, stimulation of arrested cells with insulin (10 g/ml) or IGF-I (1 nM) alone resulted in a minor increase in S-phase cells to ϳ10 -12% at 26 h. Insulin dose-response experiments in serum-free medium without ICI 182780 indicated a maximal response between 100 ng/ml and 10 g/ml insulin (data not shown), and a similar maximal response was achieved with 1 nM IGF-I. A supraphysiological concentration (10 g/ml) of insulin, known to activate both insulin and IGF-I receptor signaling in breast epithelial cells (44,45), was used in all subsequent experiments, in agreement with the design of earlier studies demonstrating synergistic effects on breast epithelial cell proliferation (15,16,46). In marked contrast, estradiol (100 nM) alone stimulated a significantly greater S-phase entry of 43%.…”
Section: Synergistic Effects Of Estradiol and Insulin/igf-i On G 1 -Ssupporting
confidence: 65%
See 1 more Smart Citation
“…1A, stimulation of arrested cells with insulin (10 g/ml) or IGF-I (1 nM) alone resulted in a minor increase in S-phase cells to ϳ10 -12% at 26 h. Insulin dose-response experiments in serum-free medium without ICI 182780 indicated a maximal response between 100 ng/ml and 10 g/ml insulin (data not shown), and a similar maximal response was achieved with 1 nM IGF-I. A supraphysiological concentration (10 g/ml) of insulin, known to activate both insulin and IGF-I receptor signaling in breast epithelial cells (44,45), was used in all subsequent experiments, in agreement with the design of earlier studies demonstrating synergistic effects on breast epithelial cell proliferation (15,16,46). In marked contrast, estradiol (100 nM) alone stimulated a significantly greater S-phase entry of 43%.…”
Section: Synergistic Effects Of Estradiol and Insulin/igf-i On G 1 -Ssupporting
confidence: 65%
“…In breast epithelial cells, insulin (13) and IGF-I (14) are potent mitogens and synergize with estrogen to stimulate cell proliferation (15,16). Several potential mechanisms have been proposed to account for these effects.…”
mentioning
confidence: 99%
“…The role of insulin in the relationship between type 2 diabetes and cancer mortality rates is supported by a biologically plausible mechanism. Insulin is a growth hormone and is known to have arthrogenic and mitogenic properties [34][35][36]. Specifically, it is suggested that hyperinsulinaemia and elevated levels of IGF-1 promote tumour cell growth in patients with type 2 diabetes [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin has been shown to stimulate the proliferation of breast cancer cells by binding and signaling through the insulin and insulinlike growth factor I (IGF-I) receptors (Milazzo et al 1992, Lai et al 2001. In addition, insulin may synergize with the mitogenic effects of estrogen (van der Burg et al 1988) and may also upregulate the expression of vascular endothelial growth factor (VEGF), a potent angiogenic agent that is secreted by breast cancer cells (Bachelder et al 2002). Moreover, adiponectin has been inversely associated with estrogen levels (Gavrila et al 2003).…”
Section: Discussionmentioning
confidence: 99%